PENINGKATAN KAPASITAS PETANI DALAM PEMANFAATAN PUPUK ORGANIK INSITU SEBAGAI EFISIENSI USAHATANI PADI SAWAH - Cecep Arief Syaripudin; Rudi Hartono; Ait Maryani (Sekolah Tinggi Pariwisata Mataram, 2020)
Utilization of Insitu organic fertilizer is one of the solutions in improving the efficiency of rice farming. At present the majority of farmers in Conggeang Sub-district are not optimal in their use of organic fertilizer. Utilization of organic fertilizer will develop better if farmers have adequate capacity. This study aims to analyze the level of capacity of farmers in the use of organic fertilizer, analyze the factors that affect the capacity of farmers, and strategies to increase the capacity of farmers in Conggeang District, Sumedang District in April to July 2020. The results of the study indicate that the level of capacity of farmers is classified as being moderate. utilization of Insitu organic fertilizer. The level of farmer's capacity is positively influenced by internal characteristics of farmers, facility support factors and extension activities. Farmers' internal characteristics consist of farmer's land area in developing farming, supporting facilities in the form of information technology availability, business capital, and availability of infrastructure, while extension activities consist of intensity of counseling, material suitability, method accuracy and instructor competence. The strategy to increase farmers' capacity is in the form of counseling activities to increase technical capacity with demonstration plots, and direct counseling using media according to field conditions.